2021
DOI: 10.3390/rs13112118
|View full text |Cite
|
Sign up to set email alerts
|

An Optimal Image–Selection Algorithm for Large-Scale Stereoscopic Mapping of UAV Images

Abstract: Recently, the mapping industry has been focusing on the possibility of large-scale mapping from unmanned aerial vehicles (UAVs) owing to advantages such as easy operation and cost reduction. In order to produce large-scale maps from UAV images, it is important to obtain precise orientation parameters as well as analyzing the sharpness of they themselves measured through image analysis. For this, various techniques have been developed and are included in most of the commercial UAV image processing software. For… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Shatangju tree. With the development of UAV technology, UAV images have also been widely used [49][50][51][52][53][54][55][56]. Studies [10][11][12][13] have shown that UAV tilt photogrammetry can quickly and conveniently obtain images and texture information of forests, pine trees, eucalyptus, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Shatangju tree. With the development of UAV technology, UAV images have also been widely used [49][50][51][52][53][54][55][56]. Studies [10][11][12][13] have shown that UAV tilt photogrammetry can quickly and conveniently obtain images and texture information of forests, pine trees, eucalyptus, etc.…”
Section: Discussionmentioning
confidence: 99%
“…We used kappa values of the EOPs to recognize image's flight direction. (Lim et al, 2021) Figure 5 explains the concept of forming image strips from kappa values. Images were classified into image strips.…”
Section: Extraction Of Tie-points Within the Same Image Stripmentioning
confidence: 99%
“…To reduce the number of image pairs, we group the overall images along their flight strips. Based on the horizontal translation of the initial orientations of images, the motion vectors of the UAV are determined as in our previous study [16].…”
Section: Tiepoint Extractionmentioning
confidence: 99%